Electroactive Polymer Actuators and Devices (EAPAD) 2007 2007
DOI: 10.1117/12.714944
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of electroactive polymer microactuators with ion-implanted electrodes

Abstract: We report on the use of the bulge test method to characterize the mechanical properties of miniaturized bucklingmode dielectric elastomer actuators (DEA). Our actuator consists of a Polydimethylsiloxane (PDMS) membrane bonded to a silicon chip with through holes. Compliant electrodes are fabricated on both sides of the membrane by metal ion implantation. The membrane buckles when a critical voltage is applied to the electrodes. The maximum displacements as well as the efficiency of such actuators strongly depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…First, the Young's modulus of metal is several order of magnitude higher than that of dielectric elastomers (50 − 100 GPa compared to 0.2 − 1 MPa), which means that even 50 nm-thick electrodes on a 50 µm-thick elastomer will have a significant stiffening impact on the elastomer, leading to a negligible actuation strain. For example, we have shown that sputtering a 8 nm gold layer on a 30.6 µm PDMS membrane with an initial Young's modulus of 0.77 MPa caused a relative increase of the Young's modulus of the membrane of 440% , up to 4.2 MPa [49]. Secondly, the limit of elasticity for metals is very low, typically 2-3% and if a metal electrode is strained above this limit, it will crack and form islands separated by non-conductive polymer.…”
Section: Metallic Thin-films Electrodesmentioning
confidence: 99%
“…First, the Young's modulus of metal is several order of magnitude higher than that of dielectric elastomers (50 − 100 GPa compared to 0.2 − 1 MPa), which means that even 50 nm-thick electrodes on a 50 µm-thick elastomer will have a significant stiffening impact on the elastomer, leading to a negligible actuation strain. For example, we have shown that sputtering a 8 nm gold layer on a 30.6 µm PDMS membrane with an initial Young's modulus of 0.77 MPa caused a relative increase of the Young's modulus of the membrane of 440% , up to 4.2 MPa [49]. Secondly, the limit of elasticity for metals is very low, typically 2-3% and if a metal electrode is strained above this limit, it will crack and form islands separated by non-conductive polymer.…”
Section: Metallic Thin-films Electrodesmentioning
confidence: 99%
“…With an acceleration potential of a few kV on the sample, the electric field accelerates the ions that then penetrate a few nm into the sample. Due to the low heat conductivity of polymers (for instance 0.22WK −1 m −1 for the Polydimethylsiloxane model Sylgard 186), thin Polydimethylsiloxane (PDMS) membranes can burn if the implantation process generates too much heat as can occur at high ion fluence [6]. The plasma can be operated in a pulsed manner to reduce charging and heating of the sample.…”
Section: Implantation Techniquesmentioning
confidence: 99%
“…We use a bulge test setup where we can apply a well defined gas differential pressure on the membrane and record its displacement with an optical profilometer [6]. With this setup we can characterize the mechanical properties of the membrane, i.e.…”
Section: Macroscopic Characterization Of Ion Implanted Deaps Thin Filmmentioning
confidence: 99%
See 2 more Smart Citations